THE CONCEPT OF ADOLESCENT EDUCATION CURRICULUM FROM THE HADITH PERSPECTIVE - Ali, Agus; Asyrofi, Asyrofi; Makmun, Syukron; Rokhim, Abdur; Mustopa, Mustopa; Jauharudin, Jauharudin; Fayadh, Muhammad (JURNAL EDUSCIENCE, 2025)
Purpose –This study aims to investigate the concept of a youth education curriculum based on Islamic hadith literature. The study is based on the idea that curriculum design should be thoroughly understood by educators, particularly by institutional leaders who engage with teenagers.Methodology – This qualitative study employs a library research design combined with a descriptive method. The key sources of information are Sahih Bukhārī, Fathul Baari, and Umdatul Qaari. Secondary materials include Tarbiyatul Awlad and an educational resource on curriculum development. Data was obtained using triangulation and the term "Anas," which refers to Anas ibn Malik, the Prophet's teenage companion. To verify the data, the double-entry method was applied, and data analysis followed a deductive approach supported by thematic categorization.Findings – The research identified 11 hadiths related to the objectives of the youth education curriculum, 403 hadiths for the content component, 25 hadiths addressing instructional strategies, and five hadiths related to evaluation. These findings suggest that the prophetic model provides a comprehensive and systematic approach to youth education, offering extensive guidance on learning goals, topic selection, teaching methods, and assessment criteria tailored to the developmental needs of teenagers.Contribution – This study advances the subject of Islamic education by providing a structured curriculum framework based on hadith. It offers significant insights for educators, curriculum creators, and institutional leaders seeking to develop exceptional youth education programs grounded in prophetic traditions and tailored to the needs of today's learners.